Cytokeratin expression in mouse lacrimal gland germ epithelium. (May 2016) - Hirayama, Masatoshi; Liu, Ying; Kawakita, Tetsuya; Shimmura, Shigeto; Tsubota, Kazuo
Abstract: Purpose: The lacrimal gland secretes tear fluids that protect the ocular surface epithelium, and its dysfunction leads to dry eye disease (DED). The functional restoration of the lacrimal gland by engraftment of a bioengineered lacrimal gland using lacrimal gland germ epithelial cells has been proposed to cure DED in mice. Here, we investigate the expression profile of cytokeratins in the lacrimal gland germ epithelium to clarify their unique characteristics. Methods: We performed quantitative polymerase chain reaction (Q-PCR) and immunohistochemistry (IHC) analysis to clarify the expression profile of cytokeratin in the lacrimal gland germ epithelium. Results: The mRNA expression of keratin (KRT) 5, KRT8, KRT14, KRT15, and KRT18 in the lacrimal gland germ epithelium was increased compared with that in mouse embryonic stem cells and the lacrimal gland germ mesenchyme, as analyzed by Q-PCR. The expression level of KRT15 increased in the transition from stem cells to lacrimal gland germ epithelium, then decreased as the lacrimal gland matured. IHC revealed that the expression set of these cytokeratins in the lacrimal gland germ epithelium was different from that in the adult lacrimal gland. The expression of KRT15 was observed in the lacrimal gland germ epithelium, and it segmentalized into some of the basal cells in the intercanulated duct in mature gland. Conclusion: We determined the expression profile of cytokeratins in the lacrimal gland epithelium, and identified KRT15 as a candidate unique cellular marker for the lacrimal gland germ epithelium. Highlights: We determined cytokeratin expression profile in lacrimal gland germ epithelium. It showed different expression pattern compared with that of adult lacrimal gland. Cytokeratin 15 was a cellular marker for the lacrimal gland germ epithelium.